2007
DOI: 10.1111/j.1474-9726.2007.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary laminopathy fibroblasts display altered genome organization and apoptosis

Abstract: SummaryA number of diseases associated with specific tissue degeneration and premature aging have mutations in the nuclear envelope proteins A-type lamins or emerin. Those diseases with A-type lamin mutation are inclusively termed laminopathies. Due to various hypothetical roles of nuclear envelope proteins in genome function we investigated whether alterations to normal genomic behaviour are apparent in cells with mutations in A-type lamins and emerin. Even though the distributions of these proteins in prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
162
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(177 citation statements)
references
References 83 publications
15
162
0
Order By: Relevance
“…It has been demonstrated that HGPS fibroblasts start acquiring a senescent phenotype at late passages (Columbaro et al, 2005; Goldman et al, 2004; Meaburn et al, 2007). We hypothesized that an altered response to stress stimuli could be a major determinant of cellular aging in those cells.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that HGPS fibroblasts start acquiring a senescent phenotype at late passages (Columbaro et al, 2005; Goldman et al, 2004; Meaburn et al, 2007). We hypothesized that an altered response to stress stimuli could be a major determinant of cellular aging in those cells.…”
Section: Resultsmentioning
confidence: 99%
“…36 Interestingly, MADA cell homozygous the R527H mutation showed the highest rates of apoptosis and micronuclei formation compared to other MADA cell carrying different types of mutation in the lamin A gene. 7 Due to the connection of micronucleation with apoptosis and considering that apoptosis could potentially account for tissue degeneration in progeria, 37 it can be speculated that the high level of phosphorylated ATM and p53 in R527H MADA cells, is responsible for the high percentage of apoptotic cells and, consequently, for the senescent phenotype. 7 The p53-associated DNA damage repair pathway constitutes a complicated network.…”
Section: Discussionmentioning
confidence: 99%
“…7 Due to the connection of micronucleation with apoptosis and considering that apoptosis could potentially account for tissue degeneration in progeria, 37 it can be speculated that the high level of phosphorylated ATM and p53 in R527H MADA cells, is responsible for the high percentage of apoptotic cells and, consequently, for the senescent phenotype. 7 The p53-associated DNA damage repair pathway constitutes a complicated network. The CDKN1A gene and the GADD45 gene family have been reported to be downstream effectors of p53, required for cell cycle arrest following DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This had widespread effects on gene expression patterns, including the upregulation of a 4 Mbp region on chromosome MMU18 (Malhas, et al 2007). Likewise, in cells derived from patients with laminopathies, a similar striking alteration in chromosome position was observed, supporting a role for lamins in controlling chromosome positioning and gene expression (Meaburn, et al 2007). …”
Section: Conservation Of Chromosome Positioning In Human and Mouse Numentioning
confidence: 62%